Reporting of suicide and homicidal violence in Sri Lankan newspapers. (1st March 2011) - De Silva, P; Jayasinghe, S; De Silva, D; Mathankumar, S
Abstract : Objectives: To determine the pattern of reporting of suicides and homicidal violence in national newspapers. Methods: National newspapers in Sinhala, Tamil and English (daily and weekly issues) were studied over a period of 5 weeks. News reports relating to suicides and homicidal violence were identified and information gathered using a structured format. Results: Thirteen national newspapers (6 Sinhala [S], 2 Tamil [T] and 5 English [E]) were selected. A total of 145 (111 weekly) individual newspapers (50S, 60T and 35E) were perused. The mean of number of reports per issue of daily newspapers was 0.68 while it was 0.18 for Sunday papers. There were 40 articles each of suicide and homicide. Analysis of the contents revealed the following: 7 (17.5%) of homicide were first page articles while 2 (5%) were suicide. The method of suicide and homicide was described in detail in 25 (31.25%) articles. None contained pictures. 18 (45%) homicide articles reported punishment to assailant. 4 (10%) suicide articles acknowledged psychiatric disorder. There were no reported alternate coping strategies or solutions. None indicated how distressed persons could obtain help. Conclusion: Reporting of violence (self-directed such as suicide and homicide) are common in daily newspapers. There is a tendency to indicate mode of suicide and homicide. Alternate coping strategies are rarely mentioned and there is no indication where help could be obtained. Newspapers should be more sensitive to the implications these reports have on encouraging suicidal and homicidal behaviour.